PENGUJIAN PERFORMA ALAT SPECTRONIC 20D+ DENGAN LARUTAN KALIUM PERMANGANAT (KMNO4) - Ismail, Rohmat; Wahyuningtyas, Irma; Erlangga, Manasye; Prihatini, Esti (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
The Spectronic 20D+ is a simple spectophotometer that is still widely used in laboratories for both research and practicum activities. In order to ensure the continued accuracy of measurements, it is imperative that this instrument undergoes rigorous testing to ascertain its performance. The selection of potassium permanganate (KMnO4) as the testing solution is particularly salient in this context, given its notable advantages over conventional alternatives such as cobalt (II) chloride and potassium dichromate. These alternatives, while widely employed, are associated with a higher degree of risk and cost. The objective of this study is to ascertain the performance of the Spectronic 20D+ device when utilized with a KMnO4 solution. In this study, two units of Spectronic 20D+ were utilized, with one unit receiving a filter cleaning treatment only (PF), and the other undergoing a filter cleaning and replacement of the wolfram lamp (PFL). The maximum wavelength test yielded a value of 515 nanometers on both devices prior to the initiation of the repair process. The results of measuring the standard solution show that there is an increase in the amount of light absorbed, the slope of the line, and the coefficient of determination (R²). These were statistically tested with significantly different results on both tools after the repair process. This finding indicates that the measurement outcomes of the KMnO4 solution can serve as a reliable metric for evaluating the performance of the device before and after the repair process. Furthermore, following the restoration of the tool, the optimal linear range for KMnO4 concentration measurement was ascertained, ranging from 0 to 25 ppm. This determination was informed by the highest R2 value and the outcomes of cuvette correction testing, which yielded a consistent molar permissivity significance value as determined by the Duncan test for the five cuvettes utilized in this study.